Effects of wall shear stress in venous neointimal hyperplasia of arteriovenous fistulae. (May 2015) - Jia, Lan; Wang, Lihua; Wei, Fang; Yu, Haibo; Dong, Hongye; Wang, Bo; Lu, Zhi; Sun, Guijiang; Chen, Haiyan; Meng, Jia; Li, Bo; Zhang, Ruining; et al.
Abstract: Aim: An arteriovenous fistulae (AVF) is the preferred vascular access for maintenance haemodialysis patients. Its dysfunction is often due to venous stenosis, which is mainly caused by neointimal hyperplasia. Additionally, haemodynamic forces, especially wall shear stress (WSS), as a mechanical stimuli to venous wall have a significant role in neointimal hyperplasia. The purpose of this study was to evaluate the association between WSS and neointimal hyperplasia. Methods: An 'end‐to‐side' AVF was created between the right femoral artery and vein of canines. Canines were killed at 7 and 28 days post‐surgery. The velocity and WSS in the three‐dimensional computational model of AVF were simulated using computational fluid dynamics (CFDs). The four typical sites of the vein evaluated in this study, chosen according to the haemodynamic analysis, included the arteriovenous anastomosis (A‐V), the juxta‐anastomotic segment (J‐V), the juxta‐ligation segment (L‐V) and the proximal vein (P‐V). The specimens were haematoxylin‐eosin stained and the intima‐media thickening was then measured. Results: Neointimal hyperplasia was more obvious in the inner wall of the J‐V and L‐V (low‐and‐disturbed WSS) sites compared with the P‐V and A‐V sites, and the outer wall of the L‐V and J‐V segments (high or laminar WSS) ( P < 0.01). Conclusion: In this study, we described the haemodynamic condition in the AVF and found that neointimal hyperplasia predisposed to occur in the inner wall of venous segment near the anastomosis. We also found that not only the neointimal hyperplasia has a strong inverse correlation with WSS levels, but also is related to flow patterns. Summary at a Glance: Venous stenosis in the outflow tract of AVFs is a common cause of AVF failure. The authors describe the relationship between flow and wall shear stress upon outflow intimal hyperplasia in a non‐uraemic canine model of AVF in order to explore the mechanism of stenosis and allow further evaluation of the complex haemodynamic changes involved.